The Efficiency of Dispersing Nano-silica Particles in Epoxy Resin Using Zirconia Ball Media by Mechanical Stirring - Hanggara Sudrajat; Muhammad Abdelhafez; Choong Kooi Chee; Takahiro Hoshino; Hirotoshi Yamada (Universitas Bunda Mulia, 2017)
This paper explores the efficiency of dispersing nano-silica particles in epoxy resin using zirconia ball media by mechanical stirring. Stirring speed (RPM), the time of milling and temperature are the main parameters studied at a fixed media: total silica-epoxy volume ratio. The results show that ball media and heating aid dispersion. The stir speed and duration affects the nano-silica dispersion, given that all the other conditions (zirconia ball media to nano-silica-epoxy ratio and intermittent heating) remain constant. At low stirring speed, short stirring duration is more suitable. On the reverse, higher stirring duration is the more suitable condition to disperse nano-silica at high stirring speed of 500 rpm.Keywords: Dispersing Nano-Silica Particles, Epoxy Resin, Zirconia Ball Media, Mechanical Stirring.